The role of stylolites as a fluid conductive, in the heterogeneous carbonate reservoirs - Mohammad Nikbin; Reza Moussavi-Harami; Naser Hafezi Moghaddas; Ghasem Aghli; Farzin Ghaemi; Babak Aminshahidy (Journal of Petroleum Exploration and Production Technology)
Abstract Stylolites possess a dual function in assessing the quality of the Lower Cretaceous carbonate reservoir in the Abadan Plain, Zagros Basin. They can either operate as barriers or facilitate the flow of fluids. To investigate this, we conducted a comprehensive study using core-plug samples, thin section petrography, high-resolution computed tomography, geochemical analysis, and petrophysical evaluation. Our findings indicate that stylolite surfaces can enhance effective porosity and connectivity by acting as open pathways. In the Fahliyan Formation, stylolites can be classified into four types based on their characteristics, including shape, size, amplitude, and the presence of insoluble material in the seams. The genetic type of stylolites is determined by the dominant stress direction, while various parameters in the burial diagenetic stage, such as pressure, temperature, and the presence of soluble ion-rich fluids, can affect porosity and permeability. Stylolites in the Fahliyan facies create continuous and connected porosity for fluid flow, with their amplitude and morphology impacting reservoir quality, especially in mud-supported facies. Therefore, the presence of stylolites in mud-supported facies can improve porosity and permeability. Dissolution, reduced overburden pressure, and horizontal compression are the main factors that expose the stylolite surfaces in the Fahliyan Formation. The extent of cementation, which is the primary barrier feature, varies significantly across the Fahliyan Reservoir in the Abadan Plain Zone due to the degree of stylolitization in the examined facies. However, our findings from wells and geological data combination indicate that reservoir quality in the examined formation facies is significantly influenced by various conditions, with a particular emphasis on the type of fluid flow in the passages.